Exploring the Factors Influencing Consumers' Purchase of National Cosmetics Based on TPB Theory - Lin, Shuyang (International Journal of Global Economics and Management, 2024)
In order to clarify the consumption status quo of national cosmetics and enhance the competitiveness of national cosmetics market, this paper conducts a study based on TPB theory, through questionnaire survey as well as spss analysis. From the attitude, subjective norms, perceived behavioral control and other factors to investigate the factors affecting consumers to buy national cosmetics. Combined with practical cases, it provides suggestions for the further development of national brands, such as differentiated tracks and multi-channel sales.